Anti-inflammatory effects of an ethanol extract of Aster glehni via inhibition of NF-κB activation in mice with DSS-induced colitis. Issue 7 (11th July 2017) - Choi, Jun-Hyeok; Chung, Kyung-Sook; Jin, Bo-Ram; Cheon, Se-Yun; Nugroho, Agung; Roh, Seong-Soo; An, Hyo-Jin
Abstract : Aster glehni had a protective effect on colonic inflammation by inactivation of NF-κB and the modulation of pathophysiological activity during DSS-induced colitis. Abstract : Although Aster glehni has been reported to prevent diabetes mellitus, hypercholesterolemia, insomnia, and cardiovascular disease, the anti-inflammatory effect of Aster glehni in colonic tissue remains unclear. In this study, we investigated the anti-inflammatory effects and the underlying molecular mechanism of an ethanol extract of Aster glehni (AG) in mice with dextran sulfate sodium (DSS)-induced colitis. AG significantly attenuated DSS-induced DAI scores, which implied that it suppressed diarrhea, gross bleeding, and the infiltration of immune cells. AG administration also effectively prevented shortening of the colon length and enlargement of the spleen size. Histological examinations indicated that AG suppressed colonic damage and the thickness of the muscle layer induced by DSS. In addition, AG inhibited the production of pro-inflammatory cytokines, such as TNF-α, IL-1β, and IL-6, and the protein expression of COX-2 and iNOS in mice with DSS-induced colitis. Administration with AG suppressed the activation of nuclear factor-κB (NF-κB) including the nuclear translocation of the p65 NF-κB subunit, phosphorylation and degradation of IκB-α. Taken together, these findings suggest that the anti-inflammatory effects of AG are mainly related to the inhibition of the expressions of inflammatory mediators via NF-κB inactivation, and support its possible therapeutic application in colitis.